Prevention of Asbestos Exposure in Latin America within a Global Public Health Perspective - Eduardo Algranti; Juan Pablo Ramos-Bonilla; Benedetto Terracini; Vilma S. Santana; Pietro Comba; Roberto Pasetto; Agata Mazzeo; Fulvio Cavariani; Andrés Trotta; Daniela Marsili (Ubiquity Press, 2019)
Background: Asbestos consumption in Latin America (LA) amounts to 10% of yearly global production. Little is known about the impact of asbestos exposure in the region. Objective: To discuss scientific and socio-economic issues and conflicts of interest and to summarize epidemiological data of asbestos health effects in LA. Discussion: Recent data on chrysotile strengthened the evidence of its carcinogenicity and showed an excessive risk of lung cancer at cumulative exposure levels as low as 1.5 fibre-years/ml. Technology for substitution is available for all asbestos-containing products and ceasing asbestos production and manufacturing will not result in unemployment and loss of income, except for the mining industry. The flawed arguments used by the industry to maintain its market, both to the public and in courtrooms, strongly relies on the lack of local evidence of the ill effects and on the invisibility of asbestos-related diseases in LA, due to the limited number of studies and the exposed workers' difficulty accessing health services. The few epidemiological studies available show clear evidence of clusters of mesothelioma in municipalities with a history of asbestos consumption and a forecasted rise in its incidence in Argentina and Brazil for the next decade. In Brazil, non-governmental organizations of asbestos workers were pivotal to counterbalance misinformation and inequities, ending recently in a Supreme Court decision backing an asbestos ban. In parallel, continuous efforts should be made to stimulate the growth of competent and ethical researchers to convey adequate information to the scientific community and to the general public.